Transcriptional regulation of PHT 1 involved in phosphate deficiency response in oil palm - Hamzah, Muhammad Luqman; Abdullah, Siti Nor Akmar; Mohamad Azzeme, Azzreena (Institute of Plantation Studies, Universiti Putra Malaysia, 2017)
Phosphate transporter 1 (PHT 1) proteins are responsible for acquisition of phosphate (Pi) by the plants. Pi uptake by the plant needs to across a steep concentration gradient from lower concentration in the soil usually less than 10μM into high Pi concentration inside plant cells which are in the range of 5 to 20mM. Transcription factor that regulates the transcription of PHT1 is phosphate starvation response 1 (PHR 1). In this study, 10 PHT 1 genes in oil palm were identified which are designated as EgPHT1;1 to EgPHT1;10 and two PHR 1 (EgPHR1;1 and EgPHR1;2). The profile expression of different PHT 1 and PHR 1 genes under Pi deficiency were determined by quantitative real-time PCR (qPCR). Both genes are highly expressed in root under Pi deficiency condition. Further study needs to be done to identify other proteins involved in PHT 1 regulatory pathway to fully understand the mechanism of Pi uptake in plant.